Impaired BKCa channel function in native vascular smooth muscle from humans with type 2 diabetes. Issue 1 (December 2017) - Nieves-Cintrón, Madeline; Syed, Arsalan; Buonarati, Olivia; Rigor, Robert; Nystoriak, Matthew; Ghosh, Debapriya; Sasse, Kent; Ward, Sean; Santana, Luis; Hell, Johannes; Navedo, Manuel
Abstract Large-conductance Ca2+ -activated potassium (BKCa ) channels are key determinants of vascular smooth muscle excitability. Impaired BKCa channel function through remodeling of BKCa β1 expression and function contributes to vascular complications in animal models of diabetes. Yet, whether similar alterations occur in native vascular smooth muscle from humans with type 2 diabetes is unclear. In this study, we evaluated BKCa function in vascular smooth muscle from small resistance adipose arteries of non-diabetic and clinically diagnosed type 2 diabetic patients. We found that BKCa channel activity opposes pressure-induced constriction in human small resistance adipose arteries, and this is compromised in arteries from diabetic patients. Consistent with impairment of BKCa channel function, the amplitude and frequency of spontaneous BKCa currents, but not Ca2+ sparks were lower in cells from diabetic patients. BKCa channels in diabetic cells exhibited reduced Ca2+ sensitivity, single-channel open probability and tamoxifen sensitivity. These effects were associated with decreased functional coupling between BKCa α and β1 subunits, but no change in total protein abundance. Overall, results suggest impairment in BKCa channel function in vascular smooth muscle from diabetic patients through unique mechanisms, which may contribute to vascular complications in humans with type 2 diabetes.